Analysis of Interference of PLC Control System in Finishing Area of Strip Mill - JI Li-ping (Gong-kuang zidonghua, 2011)
In view of problems of difficult connection of net wire and influence on start-up of devices because PLC control system of finishing area of one strip mill is in interferences produced by heavy-current circuits and devices, the paper analyzed interference cause and proposed corresponding anti-interference measures. The actual application result showed that the anti-interference measures have certain effect.